Village Naming By The Mbahammatta Ethnic In Fakfak District, West Papua: Ecolinguistic Study - Nelce Yohana Weripang; Nanda Saputra (Britain International for Academic Research (BIAR) Publisher, 2022)
This study aims to describe the form of local wisdom in the form of naming villages by the Mbahammatta ethnic group in Fakfak Regency, West Papua Province using ethnographic qualitative methods. The research data were obtained from four sources who are cultural owners, then the data were analyzed using descriptive analysis techniques. The results showed that the Mbahammatta ethnic community in the process of naming places was based on five forms of naming methods, namely based on the inventor, behavior, condition, number and physical form.